Pengaruh Shopping Lifestyle, Fashion Involvement, Positive Emotion, dan Money Available terhadap Impulse Buying Behavior di Rita Pasaraya Kebumen - Dian Haiditiya; Dewi Noor Susanti (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
This study aims to determine the effect of shopping lifestyle, fashion involvement, positive emotion, and money available on impulse buying behavior for consumer fashion store Rita Pasaraya Kebumen. The population in this study were users of the consumer fashion store Rita Pasaraya Kebumen. The technique of collecting data with a questionnaire using purposive sampling. The sample taken in this study are 110 respondents. The hypothesis was tested with the help of SPSS 26 for windows. The result of this study indicates that the shopping lifestyle partially negative significant effect on impulse buying behavior. The result of this study indicate that fashion involvement has a positif significant partial effect on impulse buying behavior. The result of this study indicate that positive emotion does positive partially effect impulse buying behavior. The result of this study indicates that money available does positife partially effect impulse buying behavior. The result of this study indicates that the shopping lifestyle, fashion involvement, positive emotion, and money available together have a positive and significant effect on impulse buying behavior for consumer fashion store Rita Pasaraya Kebumen. The results of this test indicate that the Adjusted R Square value is 0.274, meaning that 27% of the impulse buying behavior variable can be shopping lifestyle, fashion involvement, positive emotion, and money available, while 73% can be explained by other variables not in this research model.